Strongly Coupled Ag/Sn–SnO2 Nanosheets Toward CO2 Electroreduction to Pure HCOOH Solutions at Ampere-Level Current - Zhang, Min; Cao, Aihui; Xiang, Yucui; Ban, Chaogang; Han, Guang; Ding, Junjie; Gan, Li‑Yong; Zhou, Xiaoyuan (Nano-Micro Letters, 2023)
Electrocatalytic reduction of CO2 converts intermittent renewable electricity into value-added liquid products with an enticing prospect, but its practical application is hampered due to the lack of high-performance electrocatalysts. Herein, we elaborately design and develop strongly coupled nanosheets composed of Ag nanoparticles and Sn–SnO2 grains, designated as Ag/Sn–SnO2 nanosheets (NSs), which possess optimized electronic structure, high electrical conductivity, and more accessible sites. As a result, such a catalyst exhibits unprecedented catalytic performance toward CO2-to-formate conversion with near-unity faradaic efficiency (≥ 90%), ultrahigh partial current density (2,000 mA cm−2), and superior long-term stability (200 mA cm−2, 200 h), surpassing the reported catalysts of CO2 electroreduction to formate. Additionally, in situ attenuated total reflection-infrared spectra combined with theoretical calculations revealed that electron-enriched Sn sites on Ag/Sn–SnO2 NSs not only promote the formation of *OCHO and alleviate the energy barriers of *OCHO to *HCOOH, but also impede the desorption of H*. Notably, the Ag/Sn–SnO2 NSs as the cathode in a membrane electrode assembly with porous solid electrolyte layer reactor can continuously produce ~ 0.12 M pure HCOOH solution at 100 mA cm−2 over 200 h. This work may inspire further development of advanced electrocatalysts and innovative device systems for promoting practical application of producing liquid fuels from CO2. Highlights: 1 The strongly coupled Ag/Sn–SnO2 nanosheets (NSs) were prepared via a versatile electrochemical template strategy, and the generated electron-enriched Sn sites promote the formation of *OCHO and alleviate the energy barriers of *OCHO to *HCOOH. 2 Ag/Sn–SnO2 NSs afford a superior activity toward CO2 electroreduction with current densities up to 2000 mA cm‒2 and near-unity selectivity for formate production. 3 Ag/Sn–SnO2 NSs as the cathode in a membrane electrode assembly with porous solid electrolyte reactor enable the direct production of ~ 0.12 M pure HCOOH solution for 200 h.